Hair Dye Induced Depigmentation Turned Into Vitiligo - Majumdar Sabyasachi (Wolters Kluwer Medknow Publications, 1996)
Hair dye containing p-phenyldiamine may cause allergic contact dermatitis with resultant post inflammatory hypo-pigmentation, but its association with vitiligo is not yet known. A case of postinflammatory hypo-pigmentation due to application of a common hair dye developing later into vitiligo is reported.